PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL LEARNING CYCLE-7E PADA MATERI TRIGONOMETRI UNTUK MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS SISWA - Natalia Rosalina Rawa; Akbar Sutawidjaja; Sudirman Sudirman (Graduate School of Universitas Negeri Malang, 2016)
The aim of this research is producing learning instrument based on the model of learning cycle 7E in trigonometry which are valid, practical and effective. This research refers to the developmental model of Plomp which consists of three phases that are pleminary research, prototyping phase, and assessment phase. The quality of learning instrument based on the test of validity, practicality and effectiveness. Based on data analysis, the results are: the score validity of lesson plan and the students worksheet are 3,54 and 3,44 respectively, the score practicality of lesson plan and the students worksheet are 3,53 and 3,21 respectively, the students’ ability of mathematical connections on aspects of the connection between concepts or procedures in the same material increase from 66 to 81 with high category, the students’ ability of mathematical connections on aspects of the connection between concepts or procedures in matter different mathematics increase from 49,5 to 77,9 with the high category, and the student’s ability of mathematical connections in aspects of the connection between concepts or procedures in the context of daily life increase from 55,8 to 77,4 with the high category. The students’ ability of mathematical connections in classical increased from 57,1 to 78,8 with the high category. Thus, the instrument learning based on the models of learning cycle7E in trigonometry subject for high school students of grade 10 otherwise valid, practical and effective. Tujuan penelitian ini adalah menghasilkan perangkat pembelajaran materi trigonometri berbasis model learning cycle 7E yang valid, praktis dan efektif. Model pengembangan mengacu pada model Plomp yang terdiri atas tiga tahap yaitu, pleminary research, prototyping phase dan assessment phase. Kualitas perangkat pembelajaran didasarkan pada uji kevalidan, kepraktisan dan kefektifan. Berdasarkan analisis data, diperoleh hasil yaitu: (1) skor kevalidan RPP adalah 3,54, skor kevalidan LKS adalah 3,44, skor kevalidan instrumen penelitian adalah 3,66, (2) skor kepraktisan RPP 3,53 dan skor kepraktisan LKS 3,21, (3) kemampuan koneksi matematis siswa pada aspek koneksi antar konsep atau prosedur dalam materi yang sama mengalami peningkatan dari 66 menjadi 81 dengan kategori tinggi, kemampuan koneksi matematis siswa pada aspek koneksi antar konsep atau prosedur dalam materi matematika yang berbeda mengalami peningkatan dari 49,5 menjadi 77,9 dengan kategori tinggi, dan kemampuan koneksi matematis siswa pada aspek koneksi antar konsep atau prosedur dalam konteks kehidupan sehari mengalami peningkatan dari 55,8 menjadi 77,4 dengan kategori tinggi. Kemampuan koneksi matematis siswa secara klasikal meningkat dari 57,1 nilai 78,8 dengan kategori tinggi. Dengan demikian, perangkat pembelajaran berbasis model learning cycle 7E pada materi trigonometri untuk siswa SMA kelas X dinyatakan valid, praktis dan efektif.